Womens Autonomy and Utilization of Maternal Health Care Services - Dahal, Tulasha; Neupane, Sarswati; Chapagain, Pratikshya; Khanal, Ranjeeta (Journal of Nepal Health Research Council, 2023)
Background: Maternal health care means the health care that a woman receives during pregnancy, childbirth and postnatal period. Utilization of above service is crucial for the wellbeing of a mother and new born. The objective of the study is to find out women’s autonomy and maternal health care utilization in a community of Morang district. Methods: Cross-sectional study was conducted in the Gramthan Rural municipality which is located at Morang district. Study population was married women having at least one child under 12 month of age. Simple random sampling techniques was used to select the wards whereas purposive sampling technique was used to collect data with semi- structured interview schedule.Data analysis was done through binary logistic regression was used to findout the association between maternal health care utilization service with autonomy and demographic variables. All variables with a p-value 0.10 included in multivariate logistic regression. Results: Out of 318 women 36.5% had high level of autonomy and maternal health service was utilized by 29.2%. In bivariate analysis, women’s high level of autonomy was 2.033 times higher utilization of maternal health services than women’s with low autonomy. Respondents with unemployment, 0.528 times higher utilization of maternal health services than employment (p-value 0.011, CI 0.322-0.866). Ethnicity was also associated with utilization of maternal health services. In multivariate analysis education remained associated with utilization of maternal health services (p-value 0.004, 0.015, 95% CI 1.830-23.342, 1.197-5.184). It was found that the respondents with primary and secondary level education were 65% and 24% more utilized maternal health services than illiterate. Conclusions: Both level of autonomy and maternal services utilization are not satisfactory and poor specially illiterate women in a community of morang district. Women’s autonomy should be enhance to increase maternal health care utilization. Keywords: Autonomy; maternal health care; utilization